Entrepreneurial intentions among undergraduate students in Universiti Teknologi MARA (UiTM) / Tun Hazirah Tun Hamiruzzaman, Norashimah Ahmad and Nor Azira Ayob - Tun Hamiruzzaman, Tun Hazirah; Ahmad, Norashimah; Ayob, Nor Azira (Universiti Teknologi MARA, 2020)
The issue of unemployment among graduates has brought attention to policymakers and other relevant authorities to conduct awareness on the importance of entrepreneurship. Since entrepreneurship is found to be significant for the development and well-being of society, a paradigm shift among graduates is needed to stimulate economic growth and overall development since it produces jobs and shapes innovativeness. This study examined the factors that affect entrepreneurial intention among students to determine students' willingness to engage in entrepreneurial activities in the future. The objectives of this study are to understand how the attitude towards the behavior, perceived behavioral control, and entrepreneurship education affects entrepreneurial intention. There were 208 samples involved in answering the questionnaire. The results showed that attitude towards the behavior, perceived behavioral control, and entrepreneurship education significantly influence. This study highlights the importance of regulating proper entrepreneurship education to students to improve their understanding and insights to students before they venture into entrepreneurship.